The impact of artificial sweeteners on the metabolic syndrome - Czyżewski, Filip; Baranowska, Alicja; Baranowska, Katarzyna; Filipek, Kinga; Kawka, Jakub; Muciek, Michał; Mrugała, Sebastian; Mrugała, Waldemar; Skierkowski, Bartosz; Zalewska, Natalia (Journal of Education, Health and Sport, 2024)
Introduction: Metabolic syndrome is a wide-spread disease that affects even 30% of Polish population. The mentioned syndrome consists of: glucose intolerance, obesity, dyslipidaemia and high blood pressure. Change of lifestyle, particularly diet, is a crucial part of treatment of those issues. Artificial sweeteners are low-calorie or non-nutritive substances that are made for lowering sugar amounts in sweetened beverages. The use of artificial sweeteners rises among those, who want to lower their weight. Artificial sweeteners are well known substances, but their impact on health is still a matter of studies. We want to summarize the current knowledge about their impact on metabolic syndrome and its elements. Objectives: The review and presentation of the current state of knowledge on impact of artificial sweeteners on metabolic syndrome and its components. Material and methods: Review of the studies available on open access sources at PubMed, Google Scholar, National Library of Medicine and Coachrane. Conclusions: Currently there is no evidence of positive impact of artificial sweeteners on the metabolic syndrome. Moreover, new studies prove a negative impact of those substances at obesity, glucose intolerance, dyslipidaemia and blood pressure. However there is a need of further studies about physiology of gut microbiota and current subject to strengthen current depth of evidence.